Editorial de la revista número 1 del año 2018 - Alfie, José (Revista del Hospital Italiano de Buenos Aires, 2018)
In the Letter to the Editor, Susana Domínguez reports the results of a study suggesting a relationship between tinnitus as an indicator of synaptic disconnection in the cochlea in adolescents exposed to high levels of environmental noise.Sabrina Bassi presents a collaborative study between the National University of the Litoral and the Hospital Italiano of Buenos Aires, which analyzes, in an Argentine population, the interaction of polymorphisms in genes related to serotonergic neurotransmission, neurogenesis, and apolipoprotein E with depression. The authors found an association between polymorphisms in the SLC6A4 gene, which increases synaptic serotonin clearance, and the BDNF gene (brain-derived neurotrophic factor), which affects the plasticity and survival of central serotonergic neurons, with the risk of depression.José Luis Martín Calderón and collaborators studied the clinical-epidemiological characteristics of acute drug abuse intoxications in the emergency department of a hospital in Toledo, Spain, based on urine toxicology analysis. The most frequently detected substances were benzodiazepines, followed by cannabis and cocaine, with other substances detected less frequently. A history of alcoholism was present in 19% of cases. Neurological manifestations predominated, followed by cardiorespiratory symptoms. Suicidal intent was evident in 18% of cases.Aging brings losses and new scenarios that are not experienced equally by all. Individuals who throughout life have developed a self-concept based on social status, physical appearance, cognitive abilities, or purchasing power experience a decline in self-esteem in old age. In these individuals, identity and profession became fused, and consequently, ceasing to work implies a loss of self, with suicide attempts appearing as a desperate means to regain lost control. León Matusevich, Ana Vega, and Paula Donadio, from the Psychiatry Service, report three cases sharing narcissistic traits that limited adaptation to aging.Epidermoid cysts can arise in different parts of the body. Most (80%) are located in the ovaries and sacrum, and 7% in the head and neck, but they are uncommon in the oral cavity. Carlos Ruggeri, Elián García Pita, and Fabricio Lanard, from the Otorhinolaryngology Service, describe four cases of epidermoid cysts located in the sublingual region, the posterolateral oropharyngeal wall, and the submaxillary and submental regions.Fatigue is a very common reason for consultation. María Espósito and Diego Terceiro, from the Family and Community Medicine Service, present a clinical case in which, through a person-centered perspective and consideration of the psychosocial context, the problem was improved by refocusing on the emotional domain.Ménétrier disease is characterized by proliferation of gastric mucosal cells, decreased acid production, and gastric protein loss. It manifests with hypoalbuminemia, edema, weight loss, epigastric pain, and vomiting. In the Internal Medicine and Surgery Imaging Section, Magalí Squitín Tasende, María Daniela Frangi, and Carolina Silva, from the Pediatrics Residency, present ultrasonographic and radiological images showing gastric fold hypertrophy.In the “Hospital Italiano in Medline” section, two publications from the Internal Medicine Service are discussed. Augusto Ferraris, Fernando Vázquez, and Federico Angriman analyzed the incidence of venous thromboembolic disease in 1,008 patients who began outpatient antipsychotic treatment for the first time, in relation to the pharmacodynamic profile. María Paula Russo and María Florencia Grande Ratti studied hospital hyperglycemia using electronic medical records in a cohort of hospitalized adults between 2014 and 2015.Osvaldo Patiño, Hernán Aguilar, and Anahí Belatti, from the Kinesiology, Plastic Surgery, and Dermatology Services, provide a synthesis of the recent Pressure Ulcer Consensus, developed at the National Academy of Medicine in Buenos Aires.